Highly Translucent Chitosan-PVA Film for the Robust Bio-material Energy Harvester through Contact-Separation Mode TENG - Ravi Kumar Cheedarala; Chidambaram Ramaswami R; Nagarjuna Akula; Jung Il Song (Science and Technology: Developments and Applications Vol. 3, 2025)
Energy hunting through sustainable pathways has emerged with broad interests and pervasive impacts for addressing global energy issues and enabling feasible choices for working electronics and sensors in developing technologies for the application of wearable and implantable devices. The detection of sustainable materials from naturally available resources using a simple fabrication process is highly important for novel research. Chitosan -polyvinyl alcohol (Chs-PVA) blended films were prepared via layer-by-layer casting method using chitosan (Chs), and polyvinyl alcohol (PVA) for generating power through mechanical induction through triboelectric nanogenerators. The proposed Chs-PVA biodegradable film with (i.e. 1:1 Vol% with a thickness of 60 \(μ\)m) is facile, eco-friendly, highly flexible mechanically strong, cost-effective, and easy to scale up. FT-IR analysis of the ChS-PVA blend membrane showed the strong interactions between the amines of ChS and hydroxyl groups of PVA through chemical cross-linking by hydrogen bonding. More importantly, TENG values of ChS-PVA membranes were 3-4 orders of magnitude lower than chitosan films reported before. Layer-on-layer-cast membranes in particular exhibited high tensile strength (15.8 ± 1 MPa) and were more than three times stronger than other polyelectrolyte multilayer films. Both types of films remained stable in an acidic environment. Furthermore, the layer-on-layer-assembled films presented greater Voc and Isc values compared to stripped films. The ChS-PVA membrane displays as a functional layer to produce charges by collecting get-up-and-go through vertical contact and separation mode TENG counters to the PVDF membrane. The enhancement of Voc and Isc of ChS-PVA TENG were 244% and 1080% from ChS TENG. Where the case of PVA TENG, the enhancement of Voc and Isc were increased by 633% and 2888%, respectively due to the availability of free lone pairs on -NH2 and -OH functional groups. The projected ChS-PVA shows remarkably vigorous, and consistent energy-gathering presentations due to mechanically strong material properties of the ChS-PVA membrane using a simple solution process and has great potential for self-powered TENG systems even under various strict surroundings and in discrete medical applications without harmful effects. The novel ChS-PVA TENG is the potential candidate for satisfying the tight requirement of an optimized energy harvesting device as an alternate bio-material option for contact-separation mode TENGs.